Facile synthesis of nanosized Mn3O4 powder anodes for high capacity Lithium-Ion battery via flame spray pyrolysis - Wang, Hao; Zhao, Jiachang; Xie, Dongmei; Huang, Haiji; Rao, Pinhua; Mao, Jianfeng (Frontiers in Chemistry, 2022)
Mn3O4 powders with nanometer size are successfully synthesized by a simple one-step method via flame spray pyrolysis. The precursor droplet is generated by heating under high temperature flame with fixed flow rate, and the exothermic reaction is induced to form nanosized Mn3O4 powders. When used as anode material for lithium-ion battery, the Mn3O4 exhibits good cycling capacity and rate performance. It delivers a specific capacity of 1182 mAh g-1 over 110 cycles at a current density of 200 mA g-1, and has a high capacity of 140 mAh g-1 at 5000 mA g-1.